DEVELOPING CULTURAL LITERACY SKILLS THROUGH TRADITIONAL CULTURE INTRODUCTION ACTIVITIES: THE INQUIRY-BASED LEARNING APPROACH IN EARLY STUDENTS - Nilna Nurjanah; Mazildha Nur Maulidina; Nihayatul Luaili; Umi Masturoh (El Midad, 2025)
This study aimed to investigate the effects of the inquiry-based learning (IBL) approach integrated with traditional culture introduction activities on the cultural literacy skills of early childhood students using a hybrid method. Using an experimental research model, the study had a quasi-experimental design with pre-test and post-test control groups. It was conducted in an early childhood education center in Sumengko Village, Wringinanom District, with 4-6 year old children from two classes during the second semester of the 2024-2025 academic year. One of the groups was randomly assigned as the control group and the other as the experimental group. The learning activities for the experimental group included activities fitting the IBL approach integrated with traditional cultural elements. In the control group, lessons were carried out with conventional teaching techniques such as direct instruction and demonstration. A Cultural Literacy Assessment was used to measure the cultural literacy skills of the groups at the beginning and the end of the study. T-test and ANCOVA analyses were applied to the quantitative data using the SPSS software. At the end of the study, semi-structured interviews were conducted with 12 participants; six from each group. The interviews were analysed using thematic analysis to obtain themes and codes. The evaluation of the quantitative and qualitative findings revealed that the IBL approach integrated with traditional culture activities had improved the cultural literacy skills of the experimental group students..